IMPLEMENTATION OF CULTURALLY RESPONSIVE TEACHING TO IMPROVE SCIENTIFIC EXPLANATION SKILLS OF JUNIOR HIGH SCHOOL STUDENTS - Fenti Defita Sari; Habiddin Habiddin; Rudiyanto Rudiyanto (STKIP Citra Bakti, 2026)
Scientific explanation is a crucial skill in science learning as it enables students to explain related phenomena scientifically through claims, evidence, and reasoning. However, 8th-grade students’ performance at SMP Sriwedari Malang in terms of scientific explanation skills is still insufficient. This research aimed to describe how students’ scientific explanation skills were enhanced after experiencing the Culturally Responsive Teaching (CRT) approach. Employing a one-group pretest-posttest design, the research involved seven eighth-grade students at SMP Sriwedari Malang in the 2024/2025 academic year. Data were collected through essay tests aligned with three indicators, claims, evidence, and reasoning. The data analyzed using N-gain formula and the parametric paired sample t-test. The results show an increase in the average score from 55.10 (pretest) to 83.93 (posttest). The N-gain score of 0.65, which falls into the medium category, and a paired sample t-test significance value of 0.004, confirms the effectiveness of this approach. These findings indicates that the Culturally Responsive Teaching (CRT) approach effectively improves lower secondary school students’ scientific explanation skills. The study contributes theoretically and practically by highlighting the significance of integrating local cultural context into science learning to foster 21st-century skills.